Improvement of storage quality of strawberries by pullulan coatings incorporated with cinnamon essential oil nanoemulsion. (March 2020) - Chu, Yifu; Gao, ChengCheng; Liu, Xiaoya; Zhang, Ni; Xu, Tian; Feng, Xiao; Yang, Yuling; Shen, Xinchun; Tang, Xiaozhi
Abstract: This study was aimed at evaluating the effect of pullulan coating incorporated with cinnamon essential oil (CEO) nanoemulsion on the shelf life and senescence of fresh strawberries during room storage. Pullulan-CEO nanoemulsion prepared using ultrasound treatment had smaller particle size (162.1 nm) and more uniform distribution of oil droplets. After six days of storage, pullulan-CEO nanoemulsion coating remarkably lowered the loss in fruit mass, firmness, total soluble solids and titratable acidity of strawberries. In addition, pullulan-based nanoemulsion coated strawberries showed the strongest antimicrobial activity against bacteria and molds (2.544 and 1.958 log CFU/g, respectively) compared to control and pure pullulan coating groups. It is mainly due to the antimicrobial activities of CEO dispersed in nano size in pullulan matrix. This study revealed that pullulan-CEO nanoemulsion coating showed great potential to prolong the shelf life of fresh strawberries during room storage. Highlights: Pullulan-CEO nanoemulsion exhibited smaller particle size and more uniform distribution of oil droplets. Pullulan-CEO nanoemulsion coating considerably lowered the loss in physicochemical properties of strawberries. The strongest antimicrobial activity was found in Pullulan-CEO nanoemulsion coated strawberries. Pullulan-CEO nanoemulsion coating showed great potential to prolong the shelf life of strawberries during room storage.